Effects of active musical engagement during physical exercise on anxiety, pain and motivation in patients with chronic pain - Schneider, Lydia; Egle, Ulrich Tiber; Klinger, Doris; Schulz, Wolfgang; Villringer, Arno; Fritz, Thomas Hans (Frontiers in Pain Research, 2022)
The experience of anxiety is central to the development of chronic pain. Music listening has been previously shown to exert analgesic effects. Here we tested if an active engagement in music making is more beneficial than music listening in terms of anxiety and pain levels during physical activity that is often avoided in patients with chronic pain. We applied a music feedback paradigm that combines music making and sports exercise, and which has been previously shown to enhance mood. We explored this method as an intervention to potentially reduce anxiety in a group of patients with chronic pain (N = 24, 20 female and 4 men; age range 34–64, M = 51.67, SD = 6.84) and with various anxiety levels. All participants performed two conditions: one condition, Jymmin, where exercise equipment was modified with music feedback so that it could be played like musical instruments by groups of three. Second, a conventional workout condition where groups of three performed exercise on the same devices but where they listened to the same type of music passively. Participants' levels of anxiety, mood, pain and self-efficacy were assessed with standardized psychological questionnaires before the experiment and after each condition. Results demonstrate that exercise with musical feedback reduced anxiety values in patients with chronic pain significantly as compared to conventional workout with passive music listening. There were no significant overall changes in pain, but patients with greater anxiety levels compared to those with moderate anxiety levels were observed to potentially benefit more from the music feedback intervention in terms of alleviation of pain. Furthermore, it was observed that patients during Jymmin more strongly perceived motivation through others. The observed diminishing effects of Jymmin on anxiety have a high clinical relevance, and in a longer term the therapeutic application could help to break the Anxiety Loop of Pain, reducing chronic pain. The intervention method, however, also has immediate benefits to chronic pain rehabilitation, increasing the motivation to work out, and facilitating social bonding.